An improved formula for perforation of the steel plate reinforced concrete subjected to the rigid missile - Zhengyu XU (The Japan Society of Mechanical Engineers, 2019)
This paper presents an improved empirical method for the prediction of perforation of steel plate reinforced concrete barriers by rigid missiles such as aircraft engines etc. The data of rigid missile experiments newly performed in China in 2018 were collected, and numerical analysis and existing empirical methods of perforation damage analysis were compared. Based on the existing formulas, an improvement is proposed to predict the penetration effect of typical rigid projectiles on steel reinforced concrete barriers in aircraft impact or tornadoes more accurately.